Is the rubber hand illusion induced by immersive virtual reality? - Ye Yuan; Steed, Anthony (2010 IEEE Virtual Reality Conference (VR), 2010)
The rubber hand illusion is a simple illusion where participants can be induced to report and behave as if a rubber hand is part of their body. The induction is usually done by an experimenter tapping both a rubber hand prop and the participant's real hand: the touch and visual feedback of the taps must be synchronous and aligned to some extent. The illusion is usually tested by several means including a physical threat to the rubber hand. The response to the threat can be measured by galvanic skin response (GSR): those that have the illusion showed a marked rise in GSR. Based on our own and reported experiences with immersive virtual reality (IVR), we ask whether a similar illusion is induced naturally within IVR? Does the participant report and behave as if the virtual arm is part of their body? We show that participants in a HMD-based IVR who see a virtual body can experience similar responses to threats as those in comparable rubber hand illusion experiments. We show that these responses can be negated by replacing the virtual body with an abstract cursor representing the hand, and that the responses are stable under some gradual forced distortion of tracker space so that proprioceptive and visual information are not matched.